Pengaruh Kualitas Pelayanan dan Promosi Terhadap Minat Beli Pelanggan di Alfamart Medokan Sawah Kota Surabaya - Budi Pratama, Enggar; Kartika Kusmayati, Nindya; Wulansari, Dhyah (Journal Of Accounting and Business, 2024)
This study aims to investigate the influence of service quality and promotion on customer purchase intention at Alfamart Medokan Sawah, Surabaya City. The research method employed is associative, utilizing a questionnaire administered to 65 respondents using a Likert scale. Data collected were analyzed using SPSS version 21 software, including tests for validity, reliability, multiple regression analysis, t-tests, F-tests, and coefficient of determination. The research findings indicate that service quality (X1) and promotion (X2) significantly and positively influence customer purchase intention (Y) at Alfamart Medokan Sawah. Multiple regression analysis yielded the equation Y = 8.883 + 0.282X1 + 0.323X2, demonstrating that improvements in service quality and effective promotional strategies contribute significantly to increased customer purchase intention. With an R Square contribution of 79.4%, the study suggests that a substantial portion of the variation in customer purchase intention can be explained by variables related to service quality and promotion. Practically, this study can serve as a reference for retail business practitioners in formulating more targeted strategies to enhance competitiveness. Academically, this study contributes to the development of literature on factors influencing customer purchase intention, particularly in the context of modern retail.